Transformation of marine protist Diplonema papillatum - characterization of selected cell lines - Graf, Lena (Jihočeská univerzita, 2020)
The aim of this thesis was to analyze and characterize selected transformant cell lines of marine protist Diplonema papillatum.
Transformation of marine protist Diplonema papillatum - characterization of selected cell lines
Keywords: Diplonema papillatum; marine protist; gene tagging; gene replacement; Diplonema papillatum; marine protist; gene tagging; gene replacement